2021
DOI: 10.1101/2021.09.13.21263535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroresponse to SARS-CoV-2 vaccines among maintenance dialysis patients over six months

Abstract: Background and Objectives: While most maintenance dialysis patients exhibit initial seroresponse to vaccination, concerns remain regarding the durability of this antibody response. This study evaluated immunity over time. Design, setting, participants, and measurements: This retrospective cohort study included maintenance dialysis patients from a midsize national dialysis provider who received a complete SARS-CoV-2 vaccine series and had at least one antibody titer checked after full vaccination. Immunoglobuli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…While the Ab level needed for protection is not established yet, there is a correlation between seroimmunity and protection from infection as well as seroimmunity and the likelihood of transmission. 19 Therefore, this declining trend, with data demonstrating up to 95% decline in Ab levels depending on the antigenic target, supports the need for boosters and serologic monitoring moving forward to identify low responders and timely need for additional booster administration.…”
Section: Declining Ab Levels Post-mrna Vaccinationmentioning
confidence: 86%
See 1 more Smart Citation
“…While the Ab level needed for protection is not established yet, there is a correlation between seroimmunity and protection from infection as well as seroimmunity and the likelihood of transmission. 19 Therefore, this declining trend, with data demonstrating up to 95% decline in Ab levels depending on the antigenic target, supports the need for boosters and serologic monitoring moving forward to identify low responders and timely need for additional booster administration.…”
Section: Declining Ab Levels Post-mrna Vaccinationmentioning
confidence: 86%
“…29,45 Moreover, the robustness of initial Ab response postvaccination is reported to predict rapidity of Ab titer decline. 19 Those with higher maximum Ab response within 2 months from full vaccination were less likely to become seronegative or develop SARS-CoV-2 infection. 19 As such, it is important to follow the course of Ab titers several weeks after full vaccination among those with stage-specific comorbidities in order to predict better when best to give additional booster vaccine doses and ensure appropriate protection.…”
Section: Comorbiditiesmentioning
confidence: 96%
“…We recently showed that more than half of fully vaccinated patients' antibodies wane by 4-6 months, particularly among those whose initial response was not maximal based on our assay. 12 The association of low or undetectable antibody levels with breakthrough COVID-19 supports potential use of antibody levels for guiding vaccination practices, and routinely monitoring COVID-19 vaccine seroresponse via SAb-IgG levels may identify patients at risk for COVID-19 infection. A similar model already exists for maintenance dialysis patients with Hepatitis B antibody monitoring.…”
Section: Sab-igg Level and Breakthrough Covid-19mentioning
confidence: 92%
“…5,6,9 We previously reported that 10-15% of dialysis patients were non-responders to 2 doses of mRNA vaccines. 3,12 Recognizing this vulnerability, France authorized a third dose of SARS-CoV-2 mRNA vaccine for dialysis patients, 13 reporting that a third dose of BNT162b2/Pfizer vaccine promoted seroconversion in more than half of initially non-responding dialysis patients. 14 Breakthrough COVID-19 cases and COVID-19 related hospitalizations among fully vaccinated dialysis patients increased when delta variant became dominant, potentially superimposing a more virulent strain on waning immunity, as most dialysis patients were vaccinated March or earlier.…”
Section: Sab-igg Level and Breakthrough Covid-19mentioning
confidence: 99%
See 1 more Smart Citation